Validation of whole slide imaging for frozen section diagnosis in surgical pathology - Thomas W Bauer; Renee J Slaw; Jesse K McKenney; Deepa T Patil (Elsevier, 2015)
Background: Whole slide imaging (WSI) using high-resolution scanners is gaining acceptance as a platform for consultation as well as for frozen section (FS) evaluation in surgical pathology. We report results of an intra-observer concordance study comparing evaluation of WSI of scanned FS microscope slides with the original interpretation of the same microscope slides after an average lag time of approximately 1-year. Methods: A total of 70 FS cases (148 microscope slides) originally interpreted by 2 pathologists were scanned at ×20 using Aperio CS2 scanner (Leica Biosystems, San Diego, CA, USA). Reports were redacted such that the study pathologists reviewed images using eSlide Manager Healthcare Network application (Leica Biosystems) accompanied by the same clinical information available at the time of original FS evaluation. Discrepancies between the original FS diagnosis and WSI diagnosis were categorized as major (impacted patient care) or minor (no impact on patient care). Results: Lymph nodes, margins for head and neck cancer resections, and arthroplasty specimens to exclude infection, were the most common FS specimens. The average wash-out interval was 380 days (range: 303-466 days). There was one major discrepancy (1.4% of 70 cases) where the original FS was interpreted as severe squamous dysplasia, and the WSI FS diagnosis was mild dysplasia. There were two minor discrepancies; one where the original FS was called focal moderate squamous dysplasia and WSI FS diagnosis was negative for dysplasia. The second case was an endometrial adenocarcinoma that was originally interpreted as Federation of Gynecology and Obstetrics (FIGO) Grade I, while the WSI FS diagnosis was FIGO Grade II. Conclusions: These findings validate and support the use of WSI to provide interpretation of FS in our network of affiliated hospitals and ambulatory surgery centers.